Planning sustainable cities : global report on human settlements 2009 - United Nations Human Settlements Programme (London ; Sterling, VA : Earthscan, 2009)
This publication reviews recent urban planning practices and approaches, discusses constraints and conflicts therein, and identifies innovative approaches that are more responsive to current challenges of urbanization. It notes that traditional approaches to urban planning (particularly in developing countries) have largely failed to promote equitable, efficient and sustainable human settlements and to address twenty-first century challenges, including rapid urbanization, shrinking cities and aging, climate change and related disasters, urban sprawl and unplanned peri-urbanization, as well as urbanization of poverty and informality. It concludes that new approaches to planning can only be meaningful, and have a greater chance of succeeding, if they effectively address all of these challenges, are participatory and inclusive, as well as linked to contextual socio-political processes.--Publisher's description
pt. 1. Challenges and context. Urban challenges and the need to revisit urban planning -- Understanding the diversity of urban contexts -- pt. 2. Global trends : the urban planning process (procedural). The emergence and spread of contemporary urban planning -- The institutional and regulatory framework for planning -- Planning, participation and politics -- pt. 3. Global trends : the content of urban plans (substantive). Bridging the green and brown agendas -- Planning and informality -- Planning, spatial structure of cities and provision of infrastructure -- pt. 4. Global trends : monitoring evaluation and education. The monitoring and evaluation of urban plans -- Planning education -- pt. 4. Future policy directions. Towards a new role for urban planning -- pt. 5. Statistical annex. Technical notes -- Data tables.
"UN HABITAT."
Includes bibliographical references (p. [275]-293) and index.
Keywords: City planning -- Environmental aspects; Urban ecology (Sociology); Sustainable development